Quill [videorecording (DVD)] = Kuīru - Sai, Yōichi, 1949-; Kobayashi, Kaoru, 1951-; Shiina, Kippei, 1964-; Kagawa, Teruyuki, 1965-; Toda, Keiko, 1957-; Ishiguro, Kengo, 1961- (Music Box Films, 2012)
The story of a yellow lab retriever guide dog for the blind named Quill. We follow Quill from the litter, his selection to become a guide, and his life with a foster family until his first birthday, followed by highly specialized schooling in guiding the sightless. He is paired with a blind man who is at first reluctant to rely on Quill. But Quill's great patience, gentleness, and skill eventually win him over and they become inseparable friends.